Impact of external carbon dose on the removal of micropollutants using methanol and ethanol in post-denitrifying Moving Bed Biofilm Reactors - Torresi, Elena; Escolà Casas, Mònica; Polesel, Fabio; Plósz, Benedek G.; Christensson, Magnus; Bester, Kai (Water research (Oxford), 2017)
Addition of external carbon sources to post-denitrification systems is frequently used in wastewater treatment plants to enhance nitrate removal. However, little is known about the fate of micropollutants in post-denitrification systems and the influence of external carbon dosing on their removal. In this study, we assessed the effects of two different types and availability of commonly used carbon sources —methanol and ethanol— on the removal of micropollutants in biofilm systems. Two laboratory-scale moving bed biofilm reactors (MBBRs), containing AnoxKaldnes K1 carriers with acclimated biofilm from full-scale systems, were operated in continuous-flow using wastewater dosed with methanol and ethanol, respectively. Batch experiments with 22 spiked pharmaceuticals were performed to assess removal kinetics. Acetyl-sulfadiazine, atenolol, citalopram, propranolol and trimethoprim were easily biotransformed in both MBBRs (biotransformations rate constants kbio between 1.2 and 12.9 L gbiomass−1 d−1), 13 compounds were moderately biotransformed (rate constants between 0.2 and 2 L gbiomass−1 d−1) and 4 compounds were recalcitrant. The methanol-dosed MBBR showed higher kbio (e.g., 1.5–2.5-fold) than in the ethanol-dosed MBBR for 9 out of the 22 studied compounds, equal kbio for 10 compounds, while 3 compounds (i.e., targeted sulfonamides) were biotransformed faster in the ethanol-dosed MBBR. While biotransformation of most of the targeted compounds followed first-order kinetics, removal of venlafaxine, carbamazepine, sulfamethoxazole and sulfamethizole could be described with a cometabolic model. Analyses of the microbial composition in the biofilms using 16S rRNA amplicon sequencing revealed that the methanol-dosed MBBR contained higher microbial richness than the one dosed with ethanol, suggesting that improved biotransformation of targeted compounds could be associated with higher microbial richness. During continuous-flow operation, at conditions representative of full-scale denitrification systems (hydraulic residence time = 2 h), the removal efficiencies of micropollutants were below 35% in both MBBRs, with the exception of atenolol and trimethoprim (>80%). Overall, this study demonstrated that MBBRs used for post–denitrification could be optimized to enhance the biotransformation of a number of micropollutants by accounting for optimal carbon sources and extended residence time. [Display omitted] •Post-denitrifying MBBRs fed with methanol or ethanol can attenuate micropollutants.•Methanol-fed MBBR showed higher biotransformation kinetics than ethanol-fed MBBR.•Methanol-fed MBBR revealed higher microbial richness than ethanol-fed MBBR.•Organic carbon enhanced removal of a number of micropollutants (via cometabolism).•Post-denitrifying systems can be optimized towards micropollutants removal.